Target, tool, tenure and timing: the four T’s limiting the impact of traditional hunting in Indonesian Papua - Pattiselanno, Freddy; Ziembicki, Mark; Nasi, Robert; Krockenberger, Andrew (Frontiers in Conservation Science, 2024)
Subsistence hunting has sustained human populations in New Guinea for millennia, without seriously affecting the highest levels of biodiversity on Earth. Recent changes to hunting practices, demographic, social and economic context and the introduction of large exotic species has significantly altered the dynamic of hunting and its potential effects in north-west New Guinea. In this paper we examine contemporary hunting practices of six ethnic groups from highland to coastal sites throughout Papua and West Papua provinces of Indonesia. Semistructured interviews were used to examine hunting practices as well as customary rules and attitudes associated with hunting in the region and how they have changed in living memory. Each group indicated traditional restrictions on at least one of target, tool, timing or tenure, albeit in varied ways. Six different hunting tools were used and each hunter typically combined several tools while hunting. Religious and cultural factors deeply influenced hunting practices among the communities. We discuss the implications of these findings and conclude with recommendations to integrate local, village level governance and customary practices with regional and national law for more effective conservation and management of wildlife in the region while simultaneously respecting cultural heritage and local ecological knowledge. and Puertas 2000, Fa et al. 2000). Thus, the commercial wildlife trade is large throughout most of Asia, but it is now primarily providing a luxury, urban market, both for meat and body parts for traditional remedies (Bennett and Rao 2002, Corlett 2007). Many species of mammals and birds (Mack and West 2005) are hunted in Papua New Guinea by a number of ethnic groups, and all of these creatures are considered acha (edible fauna) (Dwyer 1983; Sillitoe 2001).). These included a handful of genera such as Sus, Phalanger, Spilocuscus, Dendrolagus, Zaglossus and Casuarius (Johnson et al. 2004).Hunting technological advancements and modifications such as weapons, portable lights, and vehicles have made wildlife hunting more efficient and hence dramatically raised harvest rates. The hunting mode has a significant impact on the overall take. Traditional or western hunting weaponry, snares, spotlights, and others have a significant impact on hunting success and wildlife populations (